Fluorescent protein complementation assays: new tools to study G protein-coupled receptor oligomerization and GPCR-mediated signaling - Vidi, Pierre-Alexandre (2010)
G protein-coupled receptor (GPCR) signaling is mediated by protein-protein interactions at multiple levels. The characterization of the corresponding protein complexes is therefore paramount to the basic understanding of GPCR-mediated signal transduction. The number of documented interactions involving GPCRs is rapidly growing, and appreciating the functional significance of these complexes is clearly the next challenge. New experimental approaches including protein complementation assays (PCAs) have recently been used to examine the composition, plasma membrane targeting, and desensitization of protein complexes involved in GPCR signaling. These methods also hold promise for better understanding of drug-induced effects on GPCR interactions. This review focuses on the application of fluorescent PCAs for the study of GPCR signaling. Potential applications of PCAs in high-content screens are also presented. Non-fluorescent PCA techniques as well as combined assays for the detection of ternary and quaternary protein complexes are briefly discussed.